Konsep Mental Health Semasa Pembelajaran Daring pada Mahasiswa Aceh (Studi Perspektif Al-Qur’an Berbasis Kisah Nabi Yaʿqūb) - Muhammad Furqan; Rohabdo M. Pazlan Sidauru; Hurul Maknum; Salami Mahmud; Rasyidah Rasyidah; Nurullah Nurullah; Zilva Zilva (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The reality of Covid-19 experienced by many countries, including Indonesia, has implications for changes in learning styles. Where students are required to make changes and adaptive learning. The data shows that many of the students fail to do so and are trapped in mental disorders. So this is a problem that must be addressed immediately to provide online learning. The concept of mental resilience is one way out that can be offered to solve the problem of mental disorders due to failure in adaptive learning. This concept can be explored in the Qur'ān through the story of the Prophet Yaʿqūb. This paper focuses on the concept of mental health in the Qur'anic perspective based on the story of the Prophet Yaʿqūb and the implementation of the mental health concept in the Qur'ān perspective for students during online learning. This paper uses a qualitative approach to the type of library research (library research). Data was collected by examining reading sources, namely the Qur'ān, books, journals and through documents, both written documents and electronic documents that can support the results of this study. Analysis of the data in this study using descriptive methods. The results of the study show that there are three concepts of mental health in the perspective of the Qur'ān based on the story of the Prophet Yaʿqūb, namely: 1). Be patient with Allah's qada and qadar; 2) Have a good attitude towards Allah SWT, and; 3) Put your trust in truth. Implementation of the concept of mental health from the Qur'ān perspective for Acehnese students during online learning can be done by: 1) Building patience through active confiding only to Allah through prayer and avoiding negative comments through social media; 2) Good prejudice and optimistic active response, and: 3) Tawakkal by surrendering to Allah for the results achieved.